2023
DOI: 10.3390/children10081426
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Intricate Links between Adenotonsillar Hypertrophy, Mouth Breathing, and Craniofacial Development in Children with Sleep-Disordered Breathing: Unraveling the Vicious Cycle

Luana Nosetti,
Marco Zaffanello,
Francesca De Bernardi di Valserra
et al.

Abstract: Adenotonsillar hypertrophy has been well-acknowledged as the primary instigator of sleep-disordered breathing in the pediatric population. This condition spans a spectrum, from typical age-related growth that the immune system influences to persistent pathological hypertrophy. Reduction in air spaces, metabolic changes, neurobehavioral alterations, and chronic inflammation characterizes the latter form. As the go-to treatment, adenotonsillectomy has proven effective. However, it is not a guarantee for all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…Hypotonia was the most common motor symptom in a cohort of 154 children with ASD (51%), and it appears to improve over time. In the 2-6-year-old group, the prevalence of hypotonia was approximately 63% [36] at the age in which there is a high prevalence of SDB, mainly due to adenotonsillar hypertrophy [38,39]. In general, the atonia of skeletal muscles present during REM sleep might be exacerbated by the underlying hypotonia in children [40], and in ASD might increase the risk of OSA.…”
Section: Discussionmentioning
confidence: 98%
“…Hypotonia was the most common motor symptom in a cohort of 154 children with ASD (51%), and it appears to improve over time. In the 2-6-year-old group, the prevalence of hypotonia was approximately 63% [36] at the age in which there is a high prevalence of SDB, mainly due to adenotonsillar hypertrophy [38,39]. In general, the atonia of skeletal muscles present during REM sleep might be exacerbated by the underlying hypotonia in children [40], and in ASD might increase the risk of OSA.…”
Section: Discussionmentioning
confidence: 98%
“…Drug-induced sleep endoscopy (DISE) is essential for diagnosing upper airway obstructions in OSA patients, guiding treatment decisions, and improving surgical outcomes [39]. Evidence suggests a connection between upper airway obstruction and specific patterns of oral breathing stemming from craniofacial development, implying an intertwined interdependence between the two factors [40]. Improper alignment of teeth and jaw, known as malocclusion, can also contribute to SDB by restricting air passage through the nose and throat [41].…”
Section: Discussionmentioning
confidence: 99%
“…This increased nasal resistance forces individuals to switch from nasal to mouth breathing, potentially contributing to upper airway collapse and apnoea generation. Studies have shown that nasal obstruction, whether due to anatomical issues or chronic allergies, can destabilize the upper airways and worsen sleep apnoea by disrupting normal breathing patterns [48,49]. Lofaso et al demonstrated that persistent vasomotor and non-vasomotor rhinitis are risk factors for SDB and OSA [50].…”
Section: Obesity Allergic Rhinitis and Osasmentioning
confidence: 99%